Effect of fiber-rich powder prepared from mangifera pajang peels on cardiovascular factors in hypercholesterolemic model. - Ismail, Amin; Abdulrahman Hassan, Fouad; Abdul Hamid, Azizah; Azlan, Azrina (2011)
The potential hypolipidemic effect of a fiber rich powd,er (FRP) containing antioxidant polyphenols in a hypercholesterolemia model was investigated. Lipid profile, total antioxidant status, and malondialdehyde were measured. The antioxidant enzymes (glutathione peroxidase and superoxide dismutase) were also determined. The consumption of FRP in hypercholesterolemic condition, improved the blood lipid profile and total antiox·dant status (TAS). FRP exhibited an important hypolipidemic action, returning t acylgly 01 levels in hypercholesterolemic animals to normal values. The hypocholeste IC effect was also observed, reducing total and low-density lipoprotein cholesterol. FRP with a hypercholesterolemic diet improved the lipidemic profile and reduced lipid peroxidation, suggesting that FRP might defend against cellular damage and contribute to a reduction of cardiovascular risk and thus would put forward the potential·application of this FRP as a functional food ingredient and used in the preparation of a low calorie and high fibre diet.